Impact of problem-based laboratory experience on behavioral skills outcome of telecommunication students in polytechnics - Chinyere Theresa Ogbuanya (Konselor, 2022)
The study determined the impact of problem-based laboratory experience on the behavioral skills outcome of telecommunication students in Polytechnics in North Central Nigeria. Quasi- experimental research design was used for the study. The sample for this study comprised 282 telecommunications students in 12 polytechnics in North Central Nigeria. A questionnaire titled “Behavioural and Skills Outcomes Scale. The coefficient of internal consistency was established using Cronbach alpha and was found to be 0.73. Data collected were analyzed using Analysis of Variance, t-test and analysis of co-variance with SPSS version 22. A significant main effect of treatment was observed on the overall behavioral skills. There was non- significant effect of gender but a significant interaction between treatment conditions and gender was found out. There was no significant difference in the behavioral skills outcome based on gender, age, residence, location, religion and ethnicity. It was recommended that technical teachers should use problem bases laboratory experience in teaching and learning telecommunication in Polytechnics as well as emphasize and assess behavioural skills outcome.